Financial resilience revisited: Why consistency in regulation is now paramount - across sectors and regions, and over time - Franklin Allen; Jan Pieter Krahnen; Hélène Rey (Leibniz Institute for Financial Research SAFE, 2017)
In this paper we propose a way forward towards increased financial resilience in times of growing disagreement concerning open borders, free trade and global regulatory standards. In light of these concerns, financial resilience remains a highly valued policy objective. We wish to contribute by suggesting an agenda of concrete, do-able steps supporting an enhanced level of resilience, combined with a deeper understanding of its relevance in the public domain. First, remove inconsistencies across regulatory rules and territorial regimes, and ensure their credibility concerning implementation. Second, discourage the use of financial regulatory standards as means of international competition. Third, give more weight to pedagogically explaining the established regulatory standards in public, to strengthen their societal backing.
Keywords: 330; financial resilience; free trade; global regulatory standards